2006
DOI: 10.1007/s00406-006-0686-y
|View full text |Cite
|
Sign up to set email alerts
|

Gonadal axis hormones in psychiatric male patients after a suicide attempt

Abstract: Epidemiological and clinical studies support the view that aggressive acts like suicidal and violent behaviors share a common substrate. Certain aspects of violence in males have been related to high testosterone levels, but the relation of testosterone to attempted suicide has not been studied until now. We estimated plasma levels of testosterone (T), LH, and FSH in 80 male subjects after a suicide attempt and in whom a psychiatric assessment was done during their hospitalization. Suicide intent was evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 23 publications
0
32
4
Order By: Relevance
“…This result does not support the putative role of testosterone as a biological marker for suicidal behavior, as has been proposed by Tripodianakis et al [17] . The association of high testosterone levels with specific axis I diagnoses [20] was also contradicted by our results, which show no differences between broad axis I categories.…”
Section: Discussioncontrasting
confidence: 49%
See 2 more Smart Citations
“…This result does not support the putative role of testosterone as a biological marker for suicidal behavior, as has been proposed by Tripodianakis et al [17] . The association of high testosterone levels with specific axis I diagnoses [20] was also contradicted by our results, which show no differences between broad axis I categories.…”
Section: Discussioncontrasting
confidence: 49%
“…In male suicide attempters, aggressiveness has been associated with low testosterone levels [17] , but this finding has not been replicated [18,19] . Gustavsson et al [20] did not find any significant association between testosterone levels and suicidal behaviors or aggressive-impulsive temperament.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Regardless of these differentiations, the reversal of the gender-specific pattern of prosocial behavior in depressed suicidal patients seems to be related to a disruption of HPG axis. For instance, low testosterone levels have been reported in cerebrospinal fluid and serum in suicide attempters [62], [63]. Furthermore, suicide attempters that jumped off heights showed a trend toward lower testosterone levels without increases in luteinizing hormone, suggestive of dysfunction at the hypothalamus-pituitary level [64].…”
Section: Discussionmentioning
confidence: 99%
“…Tripodianakis et al (2007) compared testosterone levels in males admitted to hospital wards after a suicide attempt with testosterone levels in healthy males in the same age range and found that attempters had significantly lower testosterone levels compared to controls, and that the attempters who used violent methods had lower testosterone levels compared to the non-violent attempter subgroup Markianos et al (2009). examined testosterone levels in a group of male psychiatric patients who had attempted suicide by jumping, compared with a group of male subjects who were hospitalized after accidentally falling from a high height, and in healthy controls.…”
Section: Discussionmentioning
confidence: 99%